Factores de riesgo socioeconómicos y culturales que influyen en la salud bucal de los niños y adolescentes especiales que acuden al Centro de atención y desarrollo El Angel. Periodo marzo-julio 2015 - Gallegos Suquilanda, Gabriela Stefanía (2015)
The oral health in patients that suffer certain disability has been a challenge for the oral health professionals throughout the history, for the different physical and cognitive disabilities that limits the proper removal of plaque, bringing the development of oral diseases highly prevalent in this population, such as dental caries, periodontal disease and dental malocclusion. That’s why the investigation in which it was planted to determine the relationship between the socioeconomic factors and cultural risks to the levels of oral health in children and adolescents from the “Special Care Center- The Angel” that carry out a special need. A cross type descriptive study was conducted, with the implementation of three instruments: a survey on cultural risk factors, a form of data collection in order to determine the socioeconomic status of parents and also a medical history in order to determine the oral health status of children with disabilities. The sample was composed of 50 people with disabilities whose age ranged from 2 to 23 years with medium and low poverty or social class. Around 94% of the population that was studies presented dental caries. A 76% of the population earned a good IHOS (Oral Hygiene Index Simplified) and an Angle I Class was found, with a crowding dominate for these people. The study found not significant relationship between the study of variables since the sample was not homogeneous as the type of disability and in general; also it was determined that the study group has a regular oral health, with high rates of decay due to lack of specialized dental care. Key words: Disability, dental caries, DMFT (Index of decayed, missing and filled), dmft index (Index of decayed, extracted or filled), OHI (Oral Hygiene Index Simplified), dental malocclusions.